Public dignity, private turmoil: an anthropological study of celibacy and sexual intimacy in the Roman Catholic Priesthood - Anderson, Jane Estelle (Curtin University, 2003)
In the Roman Catholic Church, membership of the priesthood is confined to males who are canonically required to observe perpetual continence in celibacy. This requisite is upheld by the belief that priests mediate between God and mankind and that their “supernatural” status, reflected in celibacy, transcends the profane “natural” category of being, epitomized by sexual intimacy. Significant changes in the social and cultural contexts of the Church and the world, however, have seen increasing numbers of priests contesting this canon law from the perspective of their own, often contrary, experiences of celibacy and sexual intimacy. Calls for change have been strongly resisted by the papacy.From a perspective of social poetics, this study methodically investigates the rhetorics used by the papacy and priests with friends respectively to promote their interests in celibacy and sexual intimacy. The papacy puts forward a total and singular vision of celibacy. In contrast, priests with friends identify contradictions between the universalised vision of the papacy and their locally situated experiences, inclusive of their intimate relationships. In endeavouring to resolve these contradictions, these priests produce disjunctions that separate their rhetorics of word and deed from that of the papacy’s rhetoric.The rhetorics of the papacy and priests with friends are organized in a subset of rhetorics, namely, those that constitute faith and social order, position an individual in a social order, and radical change. Firstly, I examine how the hegemony of celibacy has been established and then eroded in ritual and in broader Catholic society. This erosion has resulted in an ideological struggle between the papacy and priests with friends. Secondly, I consider how the papacy and priests with friends construct and deconstruct morality, identity, and stereotypes within cultural intimacy. The papacy creates an abstract, universal and summarizing rhetoric of celibacy to uphold its total moral system. Priests with friends, however, construct a moral system that takes into account the complexities and contingencies of their lives and ministries. Thirdly, I examine how some of these priests use a rhetoric of radical change to promote their friendships in public. This analysis consequently indicates marked differences in each rhetorical emphasis, and shows how these disagreements produce social dissonance within the priesthood and the Church.